Cold-drawn pearlitic steel wires. (September 2016) - Borchers, Christine; Kirchheim, Reiner
Abstract: Cold-drawn pearlitic steel wires have attracted considerable interest because of their excellent combination of strength and ductility. The physical interpretation of these properties has been a subject of repeated controversial discussions in the literature. Unquestioned is the fact that during the process of cold drawing, cementite is partially dissolved, while the ferrite is obviously enriched in carbon. The debate is related to the questions why cementite is decomposed and where the carbon is accommodated. It is the aim of this work to review the relevant literature and to conciliate the controversies. Special attention is paid to the microstructural evolution during progressive cold-drawing, which eventually attains nanometer-scale in two dimensions and is essential for the evolution of the mechanical as well as electrical properties. This is all the more important as recent developments in atom probe tomography allowed to study the chemical composition on the atomic scale. A further important aspect is the path of recovery and recrystallization, accompanied by softening, during post-draw annealing. A consolidated view indicates that carbon-defect interactions play a major role in all aspects of the wire properties.